Professor também tem sentimentos:a afetividade de uma professora de inglês como língua estrangeira - Melo, Letticia Vieira de (2016)
This dissertation discusses affective elements of an EFL teacher from Goiania’s municipal education system, specifically the cycle II of a school in the northwestern part of the city. In addition, this study also investigates how this teacher perceives her own affectivity and its influence on her pedagogical practice. The paper also presents my perception as a researcher and as a teacher who works in the same school system, same cycle and same region as the participating teacher. In order to complete all the phases of this research, criteria from qualitative research were used. Thus, the guiding assumptions of the present study are grounded in the case study and some aspects of interpretative research. The data analysis is based on theoretical principles arising from Vygotsky’s (2004, 2007, 2008), Bakhtin’s (1993, 1997, 2006), Voli’s (2002) and Arnold and Brown’s (2005) thoughts. The authors address the construction of the subject, considering above all the role of language, the participation of the Other, of the social aspects and of each individual’s uniqueness, as well as the importance of considering affectivity as a relevant aspect of the subject. The analysis carried out from the data and from the relationship among them, along with the theoretical framework used, shows that the participation of an English teacher’s affectivity is so obvious that the participant herself can perceive the influence of this affectivity in the methodology adopted by her, in the kind of activities used, in her way to explain the content and to call students’ attention, in the way she interacts with each of them and with the group. The results from the data discussion also make it possible to affirm that the English teacher’s affectivity not only has influence over the environment, but also arises from oneself through the interactions with the unique individuals present in it, which occur through language. These findings lead to the perception of the uniqueness of the EFL teacher and of one’s affectivity, as well as the need to admit that emotions permeate the pedagogical work. By recognizing the significant influence of affectivity on the construction of the subject and of one’s actions, we will be able to research more and better about the matter at issue, which in turn will help us to cope better with teachers’ affectivity, thus bringing about positive results for the EFL classroom.